Estimativa de tarifação do abastecimento de água na vila residencial da Eletronorte em Tucuruí-PA - SILVA, Luana Gabrielly Pinheiro da (2024)
Raising awareness about responsible consumption is critical as freshwater is a limited resource and many regions face significant challenges of scarcity. Promoting sustainable practices in domestic, industrial and agricultural use is crucial to preserving the quality and quantity of available water. In this context, this work presented a methodology to estimate water consumption in the Vila Residencial da Eletronorte (VRE) neighborhood, Tucuruí-PA. The city, due to the lack of pricing for the resource, faces challenges in offering services that can be improved to meet the community's expectations. The typology of residences in the neighborhood varies from category A (larger houses with masonry construction) to category D (houses with less mixed construction). The methodology began with the monitoring of two residences (type B and D) with hydrometering, in the months of March and August 2023. The data were tabulated and treated with descriptive statistics. The project parameters for the water supply system were estimated and, based on this, the pricing for each residence, considering the charging scenario of the concessionaire operating in the State. The results point to unsustainable consumption by residents with per capita values reaching 11,088 L/person day (B) and 8,600 L/person day (D). The region's climate, the age of the system, possible leaks, the unsustainable consumption of residents and, mainly, the lack of tariffs may have influenced excessive consumption. According to the methodology, houses B were charged R$4,632.06 and R$5,975.61 in the months of March and August, respectively, and house D was charged R$3,595.15 and R$4,632.73 in March and August, respectively. Therefore, it is recommended to use measuring devices for effective monitoring, and to highlight the importance of sustainable awareness and water pricing as an alternative to promoting a reduction in water consumption.